2021
DOI: 10.1016/j.jds.2020.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resin infiltration application on early proximal caries lesions in vitro

Abstract: Background/purpose Resin infiltration (RI) material ICON is used in treating early proximal caries lesions, as it depends on a micro–invasive infiltration technology. This in vitro study aimed to evaluate the effect of ICON resin infiltration (RI) on early proximal caries by comparing surface roughness and hardness before and after treatment with RI using atomic force microscopy (AFM), automated microhardness testing system (AMHTS), and scanning electron microscopy (SEM) in vitro. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
2
14
0
6
Order By: Relevance
“…Overall, twelve studies included bovine teeth (n per group = 803) while twenty-five studies included human teeth (n per group = 865). Nine studies reported data without specimen demineralization previously to resin infiltration [47,54,55,57,59,[61][62][63][64]74] and thirty-nine articles included the demineralization process before the infiltrative resin [21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][48][49][50][51][52][53]56,58,60,[65][66][67][69][70][71][72][73]. The demineralization process consists of emerging the teeth in a demineralization solution, with pH between 4 and 5 for a period of time that ranges from 1 min to 1200 h, to simulate the formation of WSLs (Table…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Overall, twelve studies included bovine teeth (n per group = 803) while twenty-five studies included human teeth (n per group = 865). Nine studies reported data without specimen demineralization previously to resin infiltration [47,54,55,57,59,[61][62][63][64]74] and thirty-nine articles included the demineralization process before the infiltrative resin [21,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][48][49][50][51][52][53]56,58,60,[65][66][67][69][70][71][72][73]. The demineralization process consists of emerging the teeth in a demineralization solution, with pH between 4 and 5 for a period of time that ranges from 1 min to 1200 h, to simulate the formation of WSLs (Table…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Some concerns have been raised regarding the long term colour stability and susceptibility to staining of this technique based on in-vitro studies which need to be considered and included in treatment planning. Ulrich and colleagues found that surface roughness of tooth treated with resin infiltration technique was higher than that of sound enamel in addition to demineralized enamel and this is supported by recent studies (Ulrich et al, 2015;El-Meligy et al, 2021). The micro-roughness of resin infiltrated surface can act as a medium for extrinsic staining agents and plaque to accumulate which over time will result in significant alterations in colour.…”
Section: Discussionmentioning
confidence: 88%
“…Demineralized teeth were further classified into three subgroups, according to the type of repair material used (either being remineralized or resininfiltrated) in a single application method (9) . All teeth were stored in distilled water at 37°C until tested after 1 week.…”
Section: Ii3 Remineralization Of Teethmentioning
confidence: 99%